2021
DOI: 10.3390/jmmp5040126
|View full text |Cite
|
Sign up to set email alerts
|

FE-Simulation Based Design of Wear-Optimized Cutting Edge Roundings

Abstract: The performance of cutting tools can be significantly enhanced by matching the cutting edge rounding to the process and material properties. However, the conventional cutting edge rounding design is characterized by a significant number of experimental machining studies, which involve considerable cost, time, and resources. In this study, a novel approach to cutting edge rounding design using FEM-based chip formation simulations is presented. Based on a parameterized simulation model, tool temperatures, stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The planing test rig is used to measure the process force and to calculate the local normal stress σ and tangential stress τ at the cutting edge according to the method of Bergmann [29]. This method was used in [54] to determine the internal stresses of the cutting wedge during planing, as well in order to determine the mechanical load in wet metal cutting [55] and in combination with FE-based simulations to determine wearoptimised cutting edge microgeometries [56]. In the experiments, the cutting speed (V c ) is varied in three steps.…”
Section: Comparison With In Situ Measured Coefficient Of Friction Dur...mentioning
confidence: 99%
“…The planing test rig is used to measure the process force and to calculate the local normal stress σ and tangential stress τ at the cutting edge according to the method of Bergmann [29]. This method was used in [54] to determine the internal stresses of the cutting wedge during planing, as well in order to determine the mechanical load in wet metal cutting [55] and in combination with FE-based simulations to determine wearoptimised cutting edge microgeometries [56]. In the experiments, the cutting speed (V c ) is varied in three steps.…”
Section: Comparison With In Situ Measured Coefficient Of Friction Dur...mentioning
confidence: 99%
“…Zhao et al [18] established a simulation model of tool milling steel to optimize the tool edge parameters and conducted orthogonal tests, which showed that the depth of wear of the milling cutter decreases and then increases with the increase of the shape factor, which is consistent with the simulation results. Bergmann et al [19] proposed a new method for the design of the cutting-edge rounding angle based on the finite element simulation model and test, and the optimal value of the cutting-edge rounding angle was obtained by combining it with the wear model. Fang et al [20] investigated the effect of tool wear on cutting force and vibration in Inconel 718 turning and found that tool edge wear increases with increasing edge radius.…”
Section: Introductionmentioning
confidence: 99%
“…In the presented analysis in manufacturing companies, we came across this phenomenon, i.e., a lack of funds. This presented solution would certainly not burden the companies’ budget considerably, as it would practically only replace the active parts of the forming equipment, which would speed up this work, make it more attractive, and would make it relatively easy for any just-trained worker and increase safety at work [ 17 , 18 , 19 , 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%